2007
DOI: 10.1111/j.1472-765x.2007.02296.x
|View full text |Cite
|
Sign up to set email alerts
|

The polyphenol (−)-epicatechin gallate disrupts the secretion of virulence-related proteins by Staphylococcus aureus

Abstract: Aim:  (−)‐Epicatechin gallate (ECg) modifies the morphology, cell wall architecture and β‐lactam antibiotic susceptibility of Staphylococcus aureus. As these effects result primarily from intercalation into the bacterial cytoplasmic membrane, the capacity of ECg to modulate the secretion of two key staphylococcal virulence factors, coagulase and α‐toxin, was examined. Methods and Results:  Bioassays were used to determine coagulase and haemolysin activity in culture supernatants of a number of S. aureus isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 21 publications
(26 reference statements)
2
59
0
Order By: Relevance
“…This was demonstrated by examining supernatants from treated S. aureus cultures for the ability to coagulate blood plasma and to lyse erythrocytes. As in the study by Choi et al [20], some direct activity was detected from the flavonoid against ␣-toxin, but not enough to account for the results obtained [128]. The decrease in secretion is unlikely to be related to cell aggregation (and diminished surface area) either, because secretion of the enzyme protease was not inhibited.…”
Section: Inhibition Of Virulence Factor Secretionmentioning
confidence: 53%
See 1 more Smart Citation
“…This was demonstrated by examining supernatants from treated S. aureus cultures for the ability to coagulate blood plasma and to lyse erythrocytes. As in the study by Choi et al [20], some direct activity was detected from the flavonoid against ␣-toxin, but not enough to account for the results obtained [128]. The decrease in secretion is unlikely to be related to cell aggregation (and diminished surface area) either, because secretion of the enzyme protease was not inhibited.…”
Section: Inhibition Of Virulence Factor Secretionmentioning
confidence: 53%
“…Recent studies have shown that sub-MIC levels of flavonoid inhibit release of this bacterium's virulence factors. Shah et al found that epicatechin gallate prevents the secretion of coagulase and ␣-toxin [128]. This was demonstrated by examining supernatants from treated S. aureus cultures for the ability to coagulate blood plasma and to lyse erythrocytes.…”
Section: Inhibition Of Virulence Factor Secretionmentioning
confidence: 95%
“…At 0.015 mL mL À1 the coagulase activity found for the cells were in a range of þ (level 1) to þþ (level 2). It is probable that the much of the reduction in coagulase activity of the cells is due to a prevention of secretion of the proteins as a result of changes in the physical nature of the staphylococcal cytoplasm membrane (Shah, Stapleton, & Taylor, 2008). Moreover, the intercalation of active plant compounds into the cytoplasm membrane may interfere with membrane-associated signal transduction process (Ikigai, Toda, Okubo, Hara, & Shimamura, 1990;Okubo, Ikigai, Toda, & Shimamura, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…Together with a large reduction in the degree of a d -alanyl esterification of cell wall teichoic acid [34], exposure to ECg results in major changes to the overall electrochemical charge profile of the staphylococcal surface (Figure 2). Thus, insertion of ECg into the lipid palisade of the EMRSA-16 CM results in a suboptimal environment in which membrane proteins are forced to operate and this is likely to account for the observed disruption of protein secretion [42] and loss of capacity to form biofilms [35]. …”
Section: Discussionmentioning
confidence: 99%